2002
DOI: 10.1309/u72e-xd57-nf4j-xvg8
|View full text |Cite
|
Sign up to set email alerts
|

Dual Sampling of the Endocervix and Its Impact on AutoCyte Prep Endocervical Adequacy

Abstract: Only a few blastic natural killer (NK) cell leukemias and lymphomas have been reported. As such, the clinicopathologic spectrum of this disease is incompletely understood. We report 7 cases of blastic NK cell lymphoma/leukemia. All patients were men, 5 white and 2 Arab American. All cases exhibited blastic morphologic features and were CD3- and CD56+ with germline T-cell receptor genes. Five cases were CD4+ and involved the skin. Both CD4- cases never involved the skin. Other markers of mature NK cells such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 4 publications
1
20
1
Order By: Relevance
“…We have previously shown that use of the Surgipath C-E brush (Richmond, IL) in combination with the SurePath broom did not increase EC recovery in women undergoing a SurePath Pap [6]. This previous study, however, did not investigate whether use of an EC brush enhanced SurePath Pap diagnostic utility.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…We have previously shown that use of the Surgipath C-E brush (Richmond, IL) in combination with the SurePath broom did not increase EC recovery in women undergoing a SurePath Pap [6]. This previous study, however, did not investigate whether use of an EC brush enhanced SurePath Pap diagnostic utility.…”
Section: Resultsmentioning
confidence: 93%
“…We have previously shown that the majority (88%) of SurePath Pap limited by diagnoses are due to lack of an EC component [6]. To overcome this problem, some clinicians have turned to using additional devices (usually an EC brush) in combination with the SurePath broom to attempt to increase the EC yield.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The published data have shown that many of these issues of smear quality are improved with the utilization of liquid-based preparation. 7,8,11,13,17,18 In the present study, SurePath slides were made using residual cellular material from an endocervical brush gathered during colposcopic examination and biopsy were compared with conventional smears made initially. Overall cellularity was found to be similar, although SurePath specimens were processed following the making of the conventional smear.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12]14 Most studies have utilized endocervical broom type specimens; however, studies do show that this performance improvement also extends to specimens collected with the endocervical brush. 17 In the present study, the performance of the SurePath method for the preparation of endocervical cytology specimens was evaluated in comparison to conventionally prepared slides and follow-up histologic studies. Women who were referred for colposcopic examination and biopsy because of an abnormal result on a previous cervical smear were assessed in a split sample study.…”
Section: Comparison Of Two Preparation Methods For Endocervical Evalumentioning
confidence: 99%